Late‐stage α‐synuclein accumulation in TNWT‐61 mouse model of Parkinson's disease detected by diffusion kurtosis imaging. Issue 6 (1st February 2016) - Khairnar, Amit; Ruda‐Kucerova, Jana; Drazanova, Eva; Szabó, Nikoletta; Latta, Peter; Arab, Anas; Hutter‐Paier, Birgit; Havas, Daniel; Windisch, Manfred; Sulcova, Alexandra; Starcuk, Zenon; Király, András; et al.
Abstract: Diffusion kurtosis imaging (DKI) by measuring non‐Gaussian diffusion allows an accurate estimation of the distribution of water molecule displacement and may correctly characterize microstructural brain changes caused by neurodegeneration. The aim of this study was to evaluate the ability of DKI to detect changes induced by α‐synuclein (α‐syn) accumulation in α‐syn over‐expressing transgenic mice (TNWT‐61) in both gray matter (GM) and white matter (WM) using region of interest (ROI) and tract‐based spatial statistics analyses, respectively, and to explore the relationship between α‐syn accumulation and DKI metrics in our regions of interest. Fourteen‐month‐old TNWT‐61 mice and wild‐type (WT) littermates underwent in vivo DKI scanning using the Bruker Avance 9.4 Tesla magnetic resonance imaging system. ROI analysis in the GM regions substantia nigra, striatum, hippocampus, sensorimotor cortex, and thalamus and tract‐based spatial statistics analysis in WM were performed. Immunohistochemistry for α‐syn was performed in TNWT‐61 mice and correlated with DKI findings. We found increased kurtosis and decreased diffusivity values in GM regions such as the thalamus and sensorimotor cortex, and in WM regions such as the external and internal capsule, mamillothalamic tract, anterior commissure, cingulum, and corpus callosum in TNWT‐61 mice as compared to WT mice. Furthermore, we report for the first time that α‐syn accumulation is positively correlated with kurtosis and negatively correlated with diffusivity in the thalamus. The study provides evidence of an association between the amount of α‐syn and the magnitude of DKI metric changes in the ROIs, with the potential of improving the clinical diagnosis of Parkinson's disease. We propose diffusion kurtosis imaging as a sensitive method for detecting human α‐synuclein accumulation‐induced changes in brain tissue, which may be reflective of Parkinson disease stage. Boxplots show the averaged mean kurtosis (orange) and mean diffusivity (blue) under the results of the analysis (* p  < 0.05) in brains of wild‐type (WT) and α‐synuclein over‐expressing (TNWT‐61) mice. This approach might represent a novel biomarker for the early diagnosis of Parkinson's disease. Read theEditorial Highlight for this article on page1117 . Abstract : We propose diffusion kurtosis imaging as a sensitive method for detecting human α‐synuclein accumulation‐induced changes in brain tissue, which may be reflective of Parkinson disease stage. Boxplots show the averaged mean kurtosis (orange) and mean diffusivity (blue) under the results of the analysis (* p  < 0.05) in brains of wild‐type (WT) and α‐synuclein over‐expressing (TNWT‐61) mice. This approach might represent a novel biomarker for the early diagnosis of Parkinson's disease. Read theEditorial Highlight for this article on page1117 .